Bond Strength Between Resin Composite and Glass Ionomer ( An in Vitro Study) - Nadia M. AL-Skakir; Neam N. Al-Yousifany; Maha A. Al-Murad; Saif M. AL-Skakir (University of Mosul, College of Dentistry, 2010)
Aims: The aim of this study was to evaluate the shear bond strength of the resin composite to glass ionomer cement (sandwich technique), using different types of bonding agents. Materials and Me-thods: Sixty Teflon mold of (5mm in diameter and 4mm in height) filled with a based type of light cured glass ionomer cement, cured for (40 seconds), randomly assigned into three groups ( n=20 ) for bonding with different adhesive materials, (Single Bond, i- bond, and Te-Econom) . The bonding ap-plied for ( 15 seconds ). Second split of Teflon mold (3mm in diameter and 4mm in height ) placed on to the prepared specimen filled with a Tetric Ceram composite resin (shade A2) , cured for (40 seconds), the samples stored in distilled water at 37˚C for 24h ,then thermocycled water for ( 300 cycles) at (55±2˚C and 5±2˚C) with a dwell time of (30 seconds). The bond strength measured by using Universal Testing Machine with a Knife edge head placed at the interface between glass ionomer cement and composite at a cross head speed of 0.5mm/min. The modes of fracture were examined by a stereomicroscope at 20X magnification. Results :The data were analyzed using (ANOVA) followed by Duncan's Multiple Range Test at 5% .The Single bond total-etching adhesive material showed supe-rior bond strengths than all the other materials tested . i- bond is statistically different and showed in-termediary values. The TE-Econom showed the lowest shear bond strength rates and was inferior to the Single bond one. The failures were mainly adhesive fracture for both TE-Econom and Single bond ad-hesive materials, except for i-bond that showed 60% mixed failure. Conclusions: With the limitation of this in vitro study, the high bond strength for the total- etch (Single Bond) bonding agent not mean that self- etch adhesive systems inferior to total -etch bonding, so further studies are needed to agree that total- etch bonding agents was the better form the clinical point of view. The failures were mainly ad-hesive for Single Bond and TE-Econom bonding agents and mixed failure for i-bond self- etch bondi